DAMPAK PENDIDIKAN MULTIKULTURAL TERHADAP PEMAHAMAN KEBERAGAMAAN SISWA MADRASAH - Agusta, Erna Sari (Balai Diklat Keagamaan Jakarta, 2025)
As a country full of diversity, Indonesian people should be able to maintain national unity. However, the lack of understanding of religion has led to several cases of intolerance both among people of the same religion and those of different religions. Survey results at MTsN 28 Jakarta show that 10% of students still have intolerant attitudes. Therefore, educational innovation is needed in madrasas. This research aims to determine the form of implementation of multicultural education in intracurricular, extracurricular, and co-curricular activities and its impact on students' understanding of religion. This research was conducted on grade 7 students at MTsN 28 Jakarta in January-February 2025. This research is qualitative. Data collection was conducted through questionnaires and interviews. The types of understanding of diversity studied are multicultural, humanistic, dialogical-persuasive, and social-active understanding. The impact of multicultural education is based on the average achievement of indicators for each type of understanding of diversity, namely 70%. The research results show that multicultural education is implemented by integrating the learning process, extracurricular activities, habituation, and literacy activities. The percentage of each type of religious understanding across concepts, attitudes, and practices exceeds 70%. Meanwhile, in the role realm, it is still less than 70%. However, the average achievement of indicators for each type of diversity understanding exceeds 70%. Thus, multicultural education affects students' understanding of religion. Abstrak Sebagai negara yang penuh dengan keberagaman, penduduk Indonesia seharusnya dapat menjaga persatuan bangsa. Akan tetapi, kurangnya pemahaman keberagamaan menimbulkan beberapa kasus intoleransi baik dalam sesama agama maupun berbeda agama. Hasil survei di MTsN 28 Jakarta menunjukkan 10% siswa masih memiliki sikap intoleransi. Karenanya, diperlukan inovasi pendidikan di madrasah. Penelitian ini bertujuan untuk mengetahui bentuk implementasi pendidikan multikultural pada kegiatan intrakurikuler, ekstrakurikuler, dan kokurikuler serta dampaknya terhadap pemahaman keberagamaan siswa. Penelitian ini dilakukan pada siswa kelas 7 MTsN 28 Jakarta pada bulan Januari-Februari 2025. Penelitian ini adalah penelitian kualitatif. Pengumpulan data dilakukan dengan angket dan wawancara. Jenis pemahaman keberagaman yang diteliti adalah pemahaman multikultural, humanis, dialogis-persuasif, dan aktif-sosial. Dampak pendidikan multikultural didasarkan pada capaian rata-rata indikator tiap jenis pemahaman keberagamaan yaitu sebesar 70%. Hasil penelitian menunjukkan bahwa implementasi pendidikan multikultural dilakukan dengan pengintegrasian dalam proses pembelajaran, kegiatan ekskul, kegiatan pembiasaan dan literasi. Adapun prosentase tiap jenis pemahaman keberagamaan pada ranah konsep, sikap, dan praktik mencapai lebih dari 70%. Sedangkan pada ranah peranan masih kurang dari 70%. Akan tetapi, rata-rata capaian indikator tiap jenis pemahaman keberagaman mencapai lebih dari 70%. Dengan demikian, dapat dikatakan bahwa pendidikan multikultural berdampak pada pemahaman keberagamaan siswa.